If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 24 + 2x = -11 + -2x + -15 Reorder the terms: 24 + x + 2x = -11 + -2x + -15 Combine like terms: x + 2x = 3x 24 + 3x = -11 + -2x + -15 Reorder the terms: 24 + 3x = -11 + -15 + -2x Combine like terms: -11 + -15 = -26 24 + 3x = -26 + -2x Solving 24 + 3x = -26 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 24 + 3x + 2x = -26 + -2x + 2x Combine like terms: 3x + 2x = 5x 24 + 5x = -26 + -2x + 2x Combine like terms: -2x + 2x = 0 24 + 5x = -26 + 0 24 + 5x = -26 Add '-24' to each side of the equation. 24 + -24 + 5x = -26 + -24 Combine like terms: 24 + -24 = 0 0 + 5x = -26 + -24 5x = -26 + -24 Combine like terms: -26 + -24 = -50 5x = -50 Divide each side by '5'. x = -10 Simplifying x = -10
| -4x=-2x-8 | | x^3-5x^2-6x=0 | | -5.3=wabc-7.1 | | 4x+10=5x-15 | | 3=6+3n | | 3(8+7x)=-123 | | x-6=x+8 | | 10-9x=46-23x | | -4p+9+5p=11 | | -13x-20=-10x+85 | | 3.2s-5=7 | | 2k=4k-15 | | 104=8x | | x=4.9 | | -11=d+4 | | x-4=.25x+5 | | 81-4x=2x+9 | | x(x-4)=x^2+8x+11 | | 3x^2+23x+40=0 | | 6x+5=105-40x | | 3(1-x)=-2(1-x) | | 3x=5+y | | 4x=19.6 | | -4(t+5)+2t=-7+t | | 5x+4(5x+5)=-155 | | 6x^2-29x+35=0 | | 4x-22=78 | | 5x+5=-45 | | 2(x+7)=9x+3-7x+11 | | 5x+8y=63 | | 0.75K-5=.25K-1 | | 3(-3x-9)=-90 |